Penerapan Pembelajaran Berbasis Aktivitas Bermain untuk Meningkatkan Kemandirian Anak SLB - Yelli Fitri; Rini Adriani Auliana; Lianda Dewi Sartika; Anak Agung Ngurah Bagus Janitra Dewanta; Ayunda Wulandari; Wirdullutfi; Baiq Isti Hijriani (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service aimed to improve the independence of students in a Special School (SLB) through structured play-based learning. The main issue addressed was low student engagement and independence due to limited teaching methods. The activity was conducted through preparation, implementation, and evaluation stages by applying structured play activities such as guessing sounds and imitating animal movements. Evaluation was carried out through observation of participation, ability to follow instructions, and student independence. The results showed improvements in engagement, ability to follow instructions, and independence, indicated by reduced reliance on teacher assistance. The learning environment also became more enjoyable and interactive, encouraging students to be more active and confident. This activity provides a practical alternative for teachers to develop engaging and structured learning, and demonstrates that play-based learning can be an effective approach to enhance independence among students with special needs.